Application of Zakat toward Asnaf Fisabilillah in Universiti Teknologi MARA / Siti Nur Maisarah Mohd Sharif - Mohd Sharif, Siti Nur Maisarah (Academy of Contemporary Islamic Studies (ACIS), 2018)
Zakat is an obligation and one of the forms of worship that is demanded on every capable Muslim. And the claim is in the form of handing over some property to them which requires that as stated in the Quran. In other words, zakat is imposed on the rich and wealthy people who will be distributed to certain needy asnaf as stated in the Qur'an. Asnaf for zakat (recipient of zakat) can only be accepted by the eight groups as mentioned in surah at Taubah, verse 60 ie al-fuqara '(poor people), al-masakin (poor people), amil, muallaf, al-riqab (slaves ), al gharimin (people with debt), fisabilillah (people who fight in the way of Allah) and ibn sabil (traveling in the journey).This research is to study the application of asnaf fisabilillah in current issue and also in context of an institution. This study using qualitative method by interviews the respondent who worked as head of zakat institution in Universiti Teknologi MARA.